Comparativo de rendimiento de fertilización con dosis de Nitrógeno y Humus de Lombriz en Jatropha Curcas L. (Piñon Blanco) en el distrito de Juan Guerra - Chávez Daza, Milagros Del Pilar (2011)
The greenhouse effect caused by the accumulation in the atmosphere dioxide carbon emitted by biomass burning hydrocarbons, and others brings consequences of increased soil temperature, droughts, the melting icecaps and flooding; these phenomena affect the lives of thousands of people, family, national economies, production and agricultural and forest productivity (INIFAP, 2009). Currently is being promoted energy from the organic production, which is why several countries are encouraging oilseed crop plants with the aim of extracting the biodiesel to reduce the consumption of oil and other carbon, white pinion (Jatropha curcas L.) is a shrub with oil characteristics and properties medicines belonging to the Euphorbiaceae family, can live up to 40 years It is resistant to drought; furthermore it is a plant that unlike other oil does not compete as a food product, is also considered as soil recovery which is an alternative. In the San Martin region, through public and private institutions, are being researching and promoting the pinion in order to develop the package technology of cultivation and production of biodiesel. One of the important factors in agricultural management is plant nutrition, to provide essential plant nutrients in normal development and can reach their genetic potential. This research allowed obtain adequate fertilization for greater production cultivation under forest conditions.